Analysis of the internal morphology of the maxillary first molar through the diafanization technique - Medina Sotomayor, Priscilla (2021)
Objective: determine the internal morphology of the upper first molar in a sample obtained in Cuenca-Ecuador using the diaphanization technique. Material and Metods: n a sample of 84 upper first molars and following the Vertucci classification, the internal morphology of the root canals was analyzed using the diaphanization technique. Results: 58% of the sample had three root canals, followed by the presence of four root canals in 38% of the cases. The canal visible in figure 1 (a) of the illustration was the most frequent, only one canal was found in the mesiobuccal root. Conclusions: n the analyzed sample, there is a higher frequency of three root canals with type I configuration.